FREEWAT - FREE and open source software tools for WATer resource management: an Horizon 2020 for promoting innovative ICT tools in water management - Borsi, Iacopo; Rossetto, Rudy; Foglia, Laura (Acque Sotterranee - Italian Journal of Groundwater, 2015)
-